BUDAYA LOKAL BERAWAL DARI RUMAH SEBAGAI INSTRUMEN PENINGKATAN KUALITAS KEDISIPLINAN PELAJAR - Sam'un, Ahmad; Azhari, Anjar Pranggawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Local culture control individual behavior in entire life. Symbols, meanings, and values of local culture has been shifted. Local culture is even almost extinct so it needs to be preserved by the teenager especially students as a group of cultural heirs, such as students at MTs and MA Al-Jamil, Batukliang Utara, Lombok Tengah. Efforts to preserve local culture are carried out by giving knowledge about Sasak culture. The method of this assistance has four stages what is preparation, initial observation, implementation, and evaluation. The result of this assistance is knowledge and understanding enhancement about the symbols, meanings, and values of Sasak culture. This is initial stage to internalizing the values contained in local culture such as discipline in daily life.